Assessment of glucose levels in pregnant women with history of COVID-19 in a case-control study - Monod, Cécile; Kotzaeridi, Grammata; Eppel, Daniel; Linder, Tina; Bozkurt, Latife; Hösli, Irene; Göbl, Christian S.; Tura, Andrea (Frontiers in Physiology, 2022)
Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) infection may negatively affect glucose metabolism. This study aims to assess glucose levels, prevalence of gestational diabetes mellitus (GDM) and perinatal outcome in women with history of COVID-19. To this purpose, a group of 65 patients with history of COVID-19 and 94 control patients were retrospectively recruited among pregnant women who attended the pregnancy outpatient department between 01/2020 and 02/2022. Glucose data from an oral glucose tolerance test (OGTT), GDM status and obstetric complications were assessed. We observed no differences in average (p = 0.37), fasting (p = 0.62) or post-load glucose concentrations (60 min: p = 0.19; 120 min: p = 0.95) during OGTT. A total of 15 (23.1%) women in the COVID-19 group and 18 (19.1%) women in the control group developed GDM (p = 0.55). Moreover, caesarean section rate, weight percentiles and pregnancy outcomes were comparable between the groups (p ≥ 0.49). In conclusion, in this study we did not identify a possible impact of COVID-19 on glucose metabolism in pregnancy, especially with regard to glucose concentrations during the OGTT and prevalence of GDM.